PENGELOLAAN FASILITAS DI KEBUN BINATANG KASANG KULIM KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Monica Santania; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to determine how the facility management of Kasang Kulim Zoo Kubang Jaya Riau Province..This research was used descriptive quantitatif method to describe the issues. Where researchers tried to describe the actual condition or state by collecting data and information in the field and explain in narrative form without test hypotheses or make predictions before. While data collection techniques in this study using observation, interviews, quesioner and documentationBased on the research that has been done, the management of Kasang Kulim Zoo already well underway just that there are still some facilities that are not functioning optimally.Keywords: Facilities, Management, Kasang Kulim Zoo